Factors Influencing the Role of Farmer Groups in Increasing Rice Farm Production - Mohamad Ikbal Bahua; Syamsu Qamar Badu; Evi Hulukati; Sarson W. Pomalato; Lukman A.R. Laliyo (Jurnal Penelitian Pertanian Terapan, 2023)
The increased rice production can be realized through the role of farmer groups as a forum for farmers to plan and carry out rice farming every planting season. This study aims to identify the factors that influence the role of farmer groups in increasing rice production, and analyze how much influence these factors have on the role of farmer groups. This research uses a quantitative descriptive method. The sampling technique was carried out purposively using the Random Sampling technique, namely by taking 25% of the total population of 280 farmer group members so that the sample results were 70 people. The data of this research are primary and secondary data. Primary data were obtained through interviews using questionnaires with members of farmer groups, while secondary data were sourced from the relevant agencies. The data obtained were then analyzed using multiple linear regression analysis consisting of the F test and t test. The results showed that the factors of motivation, independence, and characteristics of the members of the farmer groups influenced the role of farmer groups in increasing rice production with a coefficient of determination (R2) of 60.1%. Meaning that the influence of other factors outside this study was only 39.9%.   Keywords:  Characteristics, farmers, motivation, production, rice, role, self-reliance